Raising active children: how family and school shape health-promoting physical activity-findings from the FAMIPASS study - Vorlíček, Michal; Dygrýn, Jan; Janda, David; Voráčová, Jaroslava; Duncan, Scott; Sigmund, Erik; Sigmundová, Dagmar (Frontiers in sports and active living, 2025)
This study investigated the combined impact of family dynamics and school environments on physical activity levels in children aged 3-9 years across distinct segments of the school day. Conducted as part of the FAMIPASS project in the Czech Republic, the study collected data in 2022 and 2023 from 502 families affiliated with 36 preschools and primary schools. The device-based monitoring of movement behaviors in children and their parents was conducted over a one-week period using ActiGraph accelerometers, complemented by detailed family questionnaires. Regression analysis revealed that parental physical activity, BMI, and education level significantly influenced children's moderate-to-vigorous physical activity, with educated parents more likely to raise active children. Active transport to school emerged as a key factor associated with higher child activity levels specifically in the time segment before school. This research underscores the role of family and school as critical arenas for promoting health and physical activity. These insights highlight the need for integrated family-school strategies to foster healthy activity habits in children, thereby laying the groundwork for a more active generation.
Keywords: recommendations for physical activity; child; accelerometry; preschool; family characteristics; movement behaviors